Japan and Okinawa : structure and subjectivity - Hook, Glenn D.; Siddle, Richard, 1959- (Sheffield Centre for Japanese Studies/Routledge series., 2003)
Japan and Okinawa provides an up-to-date, coherent and theoretically informed examination of Okinawa from the perspective of political economy and society.